KEY ASPECTS OF THE NOVEL'S DIALOGICAL STRUCTURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The novel, as a literary genre, has evolved over the centuries, gradually turning into the most complex and polyphonic form of storytelling. Unlike poetry or drama, a novel is a space where different points of view collide and interact, creating a polyphonic picture of the world. The article emphasizes that the novel, which has a z`dialogical structure, does not provide unambiguous answers, but is an open system in which meaning is formed through the interaction of various voices.